Assessment of Cooperativity in Ternary Peptide‐Cucurbit[8]uril Complexes. Issue 17 (14th March 2017) - Cavatorta, Emanuela; Jonkheijm, Pascal; Huskens, Jurriaan
Abstract: Evaluating cooperativity for cucurbit[8]uril (CB[8])‐mediated ternary complexation is required for understanding and advancing designs of such ternary self‐assembled systems. A key issue is to dissect the contributions of the binding steps of the first and second guest molecules to the overall ternary complex formation energy. This is addressed by performing concentration‐dependent titrations between CB[8] and guests by means of concentration‐dependent calorimetric and 1 H‐NMR titrations. The sensitivity of the fitting of the cumulative heat of complexation of the calorimetric titrations is evaluated in terms of fitting error and enthalpy–entropy compensation and, together with the NMR spectroscopic analysis of the separate species, non‐cooperative binding is conceived to be the most probable binding scenario. The binding behavior of CB[8] homoternary complexes is similar to CB[8] heteroternary complexes, with an enthalpy‐driven tight fit of the guests in the CB[8] cavity overcoming the entropic penalty. Also for these types of complexes, a non‐cooperative binding is the most probable. Abstract : To be cooperative, positive, negative, or not? An assessment of homoternary complexes mediated by Cucurbit[8]uril using isothermal titration calorimetry and 1 H NMR titrations.